Perceived variation of fruit traits, and preferences in African locust bean [Parkia biglobosa (Jacq.) Benth.] in Benin: implications for domestication - Houndonougbo, J. S. H.; KASSA, DAHOGA; SALAKO, Valère; Idohou, Alix Franck Rodrigue; ASSOGBADJO, ACHILLE EPHREM; GLELE KAKAÏ, A. ROMAIN LUCAS (My University, 2020)
Understanding folk classification system of perceived variation and preferences in fruit traits are necessary to effectively engage farmers in the domestication of wild edible fruit tree species. Social attributes can help to better understand perception of variation, and preferences. We focused on Parkia biglobosa (Jacq.) Benth., a valuable fruit tree in Benin, examining the folk classification systems and preferences for fruit morphotypes, and the extent to which they are related to social attributes in the two major climatic zones of its occurrence in Benin. Using random sampling, we selected 648 informants for individual semi-structured interviews which focused on recognized morphotypes, local classification system, and both desirable and undesirable traits related to pod, pulp, and seeds. Data were analyzed using relative frequency of citation, and principal component analysis. Informants used similar criteria to differentiate fruits of species including pod shape (RFC = 100%), pulp yield (RFC = 100%) and number of seeds per pod (RFC = 99.84%), color (RFC = 100%) and taste (RFC = 99.84%) of pulp as well as brightness (RFC = 99.07%) and color (RFC = 100%) of seed. Informant’s preferences were marked for fruits containing large number of seeds with larger size and of good seed quality. Sweetness of the pulp was also mentioned, though some differences were noted among gender and sociolinguistic groups. Our findings provide essential information for decision-making for effective domestication initiatives. To advance further domestication, while conserving essential genetic resources, quantitative morphological and molecular characterization of the observed variations in P. biglobosa are needed.
Keywords: African locust bean; Domestication; Agroforestry systems; West Africa